ANALISIS PENGATURAN SOFT HANDOVER OVERHEAD TERHADAP PEFORMANSI KAPASITAS TRAFIK NODE-B DI PT. TELKOMSEL PONTIANAK - Edy Chandra . (Faculty of Engineering, Universitas Tanjungpura, 2017)
ABSTRACT This research explained about the effect of traffic Node-B capacity ( we can mention BTS on GSM network) toward Soft Handover Overhead setting on 3G network that implementation in PT.Telkomsel Pontianak. Which Note-B TB. Arang Limbung 2 as sample has experienced full capacity traffic and coused many discountinuance connection on moved situation, we can see on software NetAct value Soft Handover <99% this is constituted of value that not expected from PT. Telkomsel, becouse the standard value PT. Telkomsel should more than >99%. The Soft Handover Overhead method apparoutly can gave change toward Soft Handover value is by changed parameter CPICH offset from 0 into -20. The incroased kinds of network draw the total uer. Many of user can coused slop the network quality becouse raising of interference network or traffic voice and the high data. Node-B is sets of equipment radiator and accept that gave radio service to UE, Node-B also has maximum capacity limited. When the capacity full then coused drop call and ms try attempt rejected because channel capacity Node-B total decreased and not optimum so can coused the process Soft Handover filled. The monitor of Node-B data who hs disturbance used netAct aplication and look the slop value of Note-B Soft Handover under 99%, it means so many discounnected call on moved situation. Node-B TB. Arang Limbung 2has lower value Soft Handover until <98,44% from 3 mei 2016 – 9 mei 2016. The value CPICH offset used is - 20. Which the process of Soft Handover Overhead is to increase the value CPICH offset lower than 0. The value of Soft Handover success rate total everyday is 98,44% before used Soft Handover Overhead method the total everydat increased until 99,62% Soft Handover success rate is to precentation the total success handover alloted the total handover occur, the result of this research show that the mechanism Soft Handover good after done Soft Handover Overhead method. Keyword : NetAct, CPICH offset, Soft Handover Overhead